The innexin 7 gap junction protein contributes to synchronized activity in the Drosophila antennal lobe and regulates olfactory function - Fuenzalida-Uribe, Nicolás; Hidalgo, Sergio; Silva, Bryon; Gandhi, Saurin; Vo, David; Zamani, Parham; Holmes, Todd C.; Sayin, Sercan; Grunwald Kadow, Ilona C.; Hadjieconomou, Dafni; O’Dowd, Diane K.; Campusano, Jorge M. (Frontiers in Neural Circuits, 2025)
In the mammalian olfactory bulb (OB), gap junctions coordinate synchronous activity among mitral and tufted cells to process olfactory information. In insects, gap junctions are also present in the antennal lobe (AL), a structure homologous to the mammalian OB. The invertebrate gap junction protein ShakB contributes to electrical synapses between AL projection neurons (PNs) in Drosophila. Other gap junction proteins, including innexin 7 (Inx7), are also expressed in the Drosophila AL, but little is known about their contribution to intercellular communication during olfactory information processing. In this study, we report spontaneous calcium transients in PNs grown in cell culture that are highly synchronous when these neurons are physically connected. RNAi-mediated knockdown of Inx7 in cultured PNs blocks calcium transient neuronal synchronization. In vivo, downregulation of Inx7 in the AL impairs both vinegar-induced electrophysiological calcium responses and behavioral responses to this appetitive stimulus. These results demonstrate that Inx7-encoded gap junctions functionally coordinate PN activity and modulate olfactory information processing in the adult Drosophila AL.